Reconstructing a model of Islamic education management based on the didactic values of Sheikh Muhammad Azhari al-Palimbani’s poetry - Edi Ramlan; Munir Munir; Abdurrahmansyah Abdurrahmansyah; Mohammad Syawaludin; Wijaya Wijaya (Indonesian Journal of Educational Management and Leadership, 2026)
Purpose – Strengthening students’ character remains a major challenge in the management of Islamic education amid ongoing social and moral changes. The didactic values embedded in the poetry of Sheikh Muhammad Azhari al-Palimbani offer a relevant philosophical foundation for the development of Islamic education management. This study aims to reconstruct an Islamic education management model based on the didactic values of Sheikh Muhammad Azhari al-Palimbani and to analyze its implementation in the management of character education in Islamic educational institutions. Method – This study employs a qualitative approach with a field study design. The research was conducted at several madrasahs and Islamic boarding schools (pesantren) in Palembang that implement character education grounded in Islamic values and local wisdom. Data were collected through in-depth interviews with school principals, teachers, and pesantren administrators; observations of educational activities; and document analysis. The data were analyzed using the interactive model developed by Miles, Huberman, and Saldaña, which consists of data condensation, data display, and conclusion drawing. Findings – The findings indicate that the values of etiquette and moral character are the most dominant in educational management practices, followed by monotheism, spirituality, knowledge, and social responsibility. These five values were reconstructed into an Islamic education management model comprising value-based planning, exemplary leadership-based organization, character-building-oriented implementation, spiritual awareness-based supervision, and social responsibility-based evaluation. The model was found to support the strengthening of students’ religious culture, discipline, and sense of responsibility, while fostering a more integrated system of character education governance through greater school community engagement, consistency in religious practices, and enhanced students’ social awareness.